2007
DOI: 10.1111/j.1742-4658.2007.05733.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of α‐synuclein aggregation and inhibition of pore‐like oligomer development by β‐synuclein

Abstract: In recent years, new hope for understanding the pathogenesis of Parkinson's disease (PD) and Lewy body dementia (LBD) has emerged with the discovery of mutations and duplications in the a-synuclein (a-syn) gene that are associated with rare familial forms of Parkinsonism [1][2][3]. Moreover, it has been shown that a-syn is centrally involved in the pathogenesis of both sporadic and inherited forms of PD and LBD because this molecule accumulates in Lewy bodies (LBs) [4][5][6], synapses, and axons, and its expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
165
0
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(182 citation statements)
references
References 73 publications
(151 reference statements)
15
165
0
2
Order By: Relevance
“…The final concentration of α-syn oligomers was determined by amino acid analysis. inhibitor of α-syn fibrillization 22 or by replacing monomeric α-syn by β-synuclein (β-syn), a close α-syn homolog that lacks the NAC (non-Aβ component) region, does not form fibrils 36 and inhibits α-syn fibrillization and inclusion formation in vitro 37 and in vivo, 38 respectively. Remarkably, the addition of Tolcapone significantly reduced α-syn mixture-induced toxicity in both M17 cells and primary neurons, indicating that fibrillar growth contributes to the toxic event (Figure 5a and Supplementary Figure S5A).…”
Section: Resultsmentioning
confidence: 99%
“…The final concentration of α-syn oligomers was determined by amino acid analysis. inhibitor of α-syn fibrillization 22 or by replacing monomeric α-syn by β-synuclein (β-syn), a close α-syn homolog that lacks the NAC (non-Aβ component) region, does not form fibrils 36 and inhibits α-syn fibrillization and inclusion formation in vitro 37 and in vivo, 38 respectively. Remarkably, the addition of Tolcapone significantly reduced α-syn mixture-induced toxicity in both M17 cells and primary neurons, indicating that fibrillar growth contributes to the toxic event (Figure 5a and Supplementary Figure S5A).…”
Section: Resultsmentioning
confidence: 99%
“…In this follow-up study, we identified putative multimers of two monomeric αSyn species of 14 and 17 kDa that included putative dimers (∼28 and 35 kDa), and tetramers (∼56 kDa) using a combination of biochemical techniques. The recognition of this pattern suggests the possible existence of two likely pathways for the aggregation of αSyn in vivo, a principle first suggested by molecular modeling of αSyn aggregates (36) and recently integrated into the proposed mechanisms of αSyn aggregation and propagation (3). This hypothesis is further supported by the existence of divergent detections of o-αSyn by the homotypic LB509 and heterotypic LB509-A11 pairs used for the ELISA studies, as recently reported for Aβ (37).…”
Section: Discussionmentioning
confidence: 99%
“…α-Syn was initially identified in AD brains associated with plaque formation and neurodegeneration [116,117]. The abnormal aggregation of α-syn is correlated with the neuropathological changes observed in PD and other synucleinopathies [13,118], and therefore inhibiting α-syn aggregation would be a key mechanism for preventing its toxicity.…”
Section: Immunotherapy Targeting Aβmentioning
confidence: 99%